Lithium niobate-based heterostructures : synthesis, properties and electron phenomena - Sumets, Maxim (IOP (Series). Release 5., 2018)
With the use of ferroelectric materials in memory devices and the need for high speed integrated optics devices, the interest in ferroelectric thin films continues to grow. With their remarkable properties such as energy nonvolatility, fast switching, radiative stability, and unique optoacoustic and optoelectronic properties, Lithium Niobate-Based Heterostructures: Synthesis, properties and electron phenomena, discusses why Lithium Niobate (LiNbO3) is one of the most promising of all ferroelectric materials. Based on years of study, this book presents the systematic characterization of substructure and electronic properties of a heterosystem formed in the deposition process of lithium niobate films onto the surface of silicon wafers.